PENGARUH KONSENTRASI RAGI TERHADAP KUALITAS SENSORI PADA FERMENTASI TAPAI SINGKONG DAN TAPAI KETAN - Sevina, Raisa; Anna Anggraini; Rani Anggraini; Emanauli; Fauziah Fiardilla; Bella Dwi Pasca; Yogie Zulni Pratama (JURAGAN - Jurnal Agroteknologi, 2025)
This study aims to evaluate the effect of varying yeast concentrations on the sensory quality of cassava tapai (Manihot esculenta) and black glutinous rice tapai (Oryza sativa var. glutinosa). The yeast concentrations used were 0.25%, 0.5%, 0.75%, 1%, and 1.5% based on the substrate weight. The parameters observed included taste, texture, aroma, and color, which were assessed organoleptically on the first and second days of fermentation. The results showed that yeast concentrations of 0.5% to 0.75% produced the best quality tapai in both cassava and black glutinous rice, characterized by a balanced sweet-sour taste, soft texture, and the distinctive aroma of tapai. At low yeast concentration (0.25%), fermentation was not optimal, while at higher concentrations (≥1%), over-fermentation occurred, marked by a bitter taste, excessively soft texture, and unpleasant odor. This study highlights the importance of using the appropriate yeast concentration in the tapai fermentation process to achieve optimal sensory quality.